Fertility among female hairdressers - Axmon, Anna; Rylander, Lars; Lillienberg, Linnéa; Albin, Maria; Hagmar, Lars (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'The study investigated whether working as a hairdresser has a negative impact on fertility, measured as time to pregnancy and miscarriage risk. ' ' METHODS ': 'Self-administered questionnaires were sent to 5289 Swedish hairdressers (response rate 50%) and to 5299 age-matched women from the general Swedish population (response rate 54%). Information was collected on time to pregnancy or trying time for women who had tried, but failed, to conceive at the time of the study. The outcome of the pregnancy was determined and categorized as either miscarriage or stillbirth or live birth. The hairdressers were compared with the referents with respect to these two outcomes. Within the hairdresser cohort, the effects of hair treatments, as well as physical workload and stress were investigated. ' ' RESULTS ': 'The hairdressers were less successful than the reference cohort in conceiving (fecundability ratio 0.91, 95% confidence interval 0.83–0.99). The effect was reduced after first-month conceptions were excluded, the indication being that the effect may be the result of birth control bias. Within the hairdresser cohort, a self-perceived stressful work situation seemed to prolong the time to pregnancy. No effects were found for the different chemical hair treatments. There was no cohort difference with respect to miscarriage risk (odds ratio 1.12, 95% confidence interval 0.88–1.42), but miscarriage risks were increased for most of the hair treatments and for self-perceived stressful work situations. However, none of these effects were statistically significant. ' ' CONCLUSIONS ': 'The present study indicates a negative impact on time to pregnancy and miscarriage risk for working as a hairdresser.¨
Keywords: female; fertility; hair preparations; hairdresser; reproduction; spontaneous abortion